2021
DOI: 10.1101/2021.10.28.465024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionarily divergent mTOR remodels the translatome to drive rapid wound closure and regeneration

Abstract: An outstanding mystery in biology is why some species, such as the axolotl, can scarlessly heal and regenerate tissues while most mammals cannot. Here, we demonstrate that rapid activation of protein synthesis is a unique, and previously uncharacterized, feature of the injury response critical for limb regeneration in the axolotl (A. mexicanum). By applying polysome sequencing, we identify hundreds of transcripts, including antioxidants and ribosome components, which do not change in their overall mRNA abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…The prevalent expression of ribosome-and cellular growth related genes in PSC-like cells during regeneration warranted an investigation of the role of TOR signaling in the activation or dedifferentiation or activity of stem cells in our model. As discussed above, TOR signaling has previously been implied in regeneration in many species, with a recent article demonstrating its crucial, regulatory role upstream of axolotl limb regeneration 49 . While the exact role this pathway plays in this process is not well understood, its activity seems to generally be required for regenerative stem cell proliferation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The prevalent expression of ribosome-and cellular growth related genes in PSC-like cells during regeneration warranted an investigation of the role of TOR signaling in the activation or dedifferentiation or activity of stem cells in our model. As discussed above, TOR signaling has previously been implied in regeneration in many species, with a recent article demonstrating its crucial, regulatory role upstream of axolotl limb regeneration 49 . While the exact role this pathway plays in this process is not well understood, its activity seems to generally be required for regenerative stem cell proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…The protein kinase Target of Rapamycin (TOR) has been implied in wound response and blastemal signaling in planarians, zebrafish and axolotl [49][50][51][52][53] , reviewed in 54 . Moreover, increased TOR signaling has also been observed in hypertranscriptomic cells 38 , as we observe them in the Platynereis regeneration process.…”
Section: Tor Signaling Is Required For Successful Activation Of Pscs ...mentioning
confidence: 99%
“…Nonetheless, IGF/mTOR’s establishment and outgrowth roles could share a common mechanism in broadly elevated protein translation. Intriguingly, axolotl limb resection also triggers a rapid increase in mTOR-dependent protein activation essential to initiate regeneration (Zhulyn et al, 2021). This effect is most pronounced in epidermal cells, consistent with the early role of the wound epidermis in triggering a regenerative response.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that immunity is thought to be a key factor in the great regenerative capacity of salamanders [17, 18]; (2) The liver has a robust synthetic capacity and is responsible for synthesizing 90% of all soluble proteins [19]. Recent studies have shown that rapid protein synthesis is essential for limb regeneration in salamanders [20]; (3) The liver stores the energy substance hepatic glycogen. It is well known that organ regeneration is a process that is highly dependent on energy expenditure and requires rapid metabolism of energy in the early stages of regeneration [21–23].…”
Section: Liver Regenerationmentioning
confidence: 99%